STRATEGI KEPEMIMPINAN KOLABORATIF KEPALA SEKOLAH DALAM MENINGKATKAN BUDAYA POSITIF DI LINGKUNGAN SDIT SALMAN AL-FARISY RENGASDENGKLOK - Muammar, Nadhif; Kosim, Abdul; Ramdhani, Khalid (Jurnal Ilmu Pendidikan Islam, 2025)
This study aims to analyze the collaborative leadership strategy implemented by the principal in enhancing the positive culture at SDIT Salman Al-Farisy Rengasdengklok. The research uses a qualitative approach with a case study method. Data was collected through in-depth interviews, observations, and documentation involving the principal, teachers, and students. This study focuses on how the active involvement of all school members contributes to the creation of a supportive environment for students' character development. The findings indicate that the principal, Ibu Lulu Susilowati, S.Pd.I, effectively built a positive culture through various habituation programs, such as morning literacy, Dhuha prayer, and "One Day One Ayat". The active involvement of teachers, students, and parents played a significant role in fostering a harmonious environment conducive to holistic student development. Furthermore, open communication between the principal and teachers, along with continuous monitoring, were crucial to the successful implementation of these programs. This research recommends that other schools, particularly those with an Islamic educational background, adopt collaborative leadership strategies that involve all school elements in the process of building a positive culture. This inclusive and participatory leadership approach can serve as a model for creating an educational environment that supports students' holistic growth